2020
DOI: 10.1097/aud.0000000000000968
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Otosclerosis on Middle Ear Function Assessed With Wideband Absorbance and Absorbed Power

Abstract: Objective-Wideband absorbance and absorbed power were evaluated in a group of subjects with surgically confirmed otosclerosis (Oto group), mean age 51.6 years. This is the first use of absorbed power in the assessment of middle ear disorders. Results were compared with control data from two groups of adults, one with normal hearing, (NH group) mean age of 31 years, and one that was age-and sex-matched with the Oto group and had sensorineural hearing loss (SNHL group). The goal was to assess group differences u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The duration of the BBN pulse was 116 ms, as described in Feeney et al (2017). The wideband acoustic immittance system and the click stimulus presented to the probe ear were calibrated prior to each test session, as described in Feeney et al (2020), and testing was completed within 30 min of this calibration. The BBN stimulus was calibrated at least annually using a Brϋel & Kjaer head and torso simulator (Model 4128) connected to a Brϋel & Kjaer LanXi digitizer to record the stimuli.…”
Section: Wideband Memrmentioning
confidence: 99%
“…The duration of the BBN pulse was 116 ms, as described in Feeney et al (2017). The wideband acoustic immittance system and the click stimulus presented to the probe ear were calibrated prior to each test session, as described in Feeney et al (2020), and testing was completed within 30 min of this calibration. The BBN stimulus was calibrated at least annually using a Brϋel & Kjaer head and torso simulator (Model 4128) connected to a Brϋel & Kjaer LanXi digitizer to record the stimuli.…”
Section: Wideband Memrmentioning
confidence: 99%
“…Many studies have shown reduced absorbance, or increased reflectance, in otosclerotic ears, 14 15 16 17 18 19 particularly in the low frequency band. This reduction in absorbance occurs due to increased stiffness in the system, which leads to a decreased acoustic sensitivity to low frequencies and, consequently, increased reflection.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Compared with traditional tympanometry, absorbance or reflectance measurements provide much more information on the state of the middle ear and allow more comprehensive assessment of middle-ear disorders. 12,13 Many studies have shown reduced absorbance, or increased reflectance, in otosclerotic ears, [14][15][16][17][18][19] particularly in the low frequency band. This reduction in absorbance occurs due to increased stiffness in the system, which leads to a decreased acoustic sensitivity to low frequencies and, consequently, increased reflection.…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage of WBT is the potential diagnostic utility of WAI at other static ear-canal pressures. For example, ossicular lesions might be diagnosed more accurately if WAI measurements are compared between TPP and very positive or very negative ear-canal static pressure, in which the TM and attached malleus are pushed medially or pulled distally (Hunter et al 2017; Feeney et al 2020). There may also be advantages of a wideband middle ear muscle reflex measured at TPP compared to standard reflex testing at ambient pressure and 226 Hz (Feeney et al 2017).…”
Section: Introductionmentioning
confidence: 99%